The impact of source establishment & negative eWOM on brand loyalty. - Ling, Irene Ailin. (2009)
The purpose of this study aims to establish a counter-intuitive proposition which contravenes the popular notion that consumers tend to perceive a more established source to be more trustworthy. More specifically, this study purports that when exposed to a negatively written electronic word-of-mouth (eWOM) on a chosen brand, the impact on brand loyalty is greater for the less established source (Experiment group) as compared to the more established source (Control group). To do so, a paired sampled t-test was employed to generate the means and significance level for the survey results. In the survey, a group of 71 college students were randomly divided into the Control and Experiment group. The Control group is given the more established source as its stimulus, while the Experiment group is given the less established source. Both sources contain the same piece of negative eWOM gathered from various online mediums. The findings from this study indicate and support our hypothesis; thereby establishing that the less established source which carries a negative eWOM article has effect a greater impact on the respondents’ brand loyalty towards the chosen brand. This result has exhibited the counter-intuitiveness and contradicts what used to be a popular belief.